(untitled) (Research, Society and Development, 2020)
It was aimed at approach theoretical foundations about the Conversation Circle as a qualitative methodological strategy in the production of nursing knowledge. This is a theoretical essay, which proposes the formulation of the methodological strategy of the Conversation Circle as a qualitative methodological strategy in the production of nursing knowledge, based on the circle of Culture of Paulo Freire. It provides an understanding of the need for the conversation and its potentialities, in which the actor of the research has the role of protagonist and not only a source of data for it. This space allows the subject to meet with needs, as well as to act in the reflection on the individual and collective connection with reality. It evidences the technique used as the alignment between the production of knowledge and care, expanding the nursing clinic that provides care while researching situations of community health relevance.